THE BLOG AS A COMMUNICATION TOOL IN THE ASSESSMENT OF YOUNG CONSUMERS - THE RESULTS OF EMPIRICAL RESEARCH - Magdalena Kowalska (Polityki Europejskie, Finanse i Marketing)
The aim of the article is to explore the attitudes of young people towards the use of company blogs as a communication tool between the company and clients and source of information about products and/or the company. In the first part of the article, based on the analysis of secondary sources, the history of the development of modern blogs is presented. This part also discusses the classification of blogs and the potential of the blogosphere as a virtual community as well as the numerous benefits resulting from running a corporate blog. The second part of the study presents the results of the primary research carried out among a representative sample of young people (aged 15-24), whose aim was to recognize their attitudes towards the use of corporate blogs in marketing communication.